Examining Contactless Digital Technologies (CDTs) in the Midst of the COVID-19 - Tibor Csizmadia; Nora Obermayer; Zsuzsanna Banasz (Emerging Science Journal, 2022)
The COVID-19 pandemic brought CDTs to the forefront of business life. This study provides an important insight into a specific country's context, which has not been sufficiently investigated. This paper aims 1) to investigate how companies’ general characteristics impact the use of contactless digital technologies (CDTs) in Hungary; 2) to examine employees’ attitudes regarding the use of CDTs; and 3) to explore how firms have tried to enhance employees’ acceptance of CDTs. A computer-assisted data collection (CAPI) was carried out during the coronavirus (COVID-19) period. The online questionnaire was completed by employees of Hungarian companies. Descriptive statistics and relationship analyses (Cramer's V and Kendall's Tau) were used to analyse the collected data ( ). Results indicate that 1) the general characteristics of companies, such as their profile and size, have a significant impact on the use of CDTs; 2) the typical attitude of employees towards CDTs is rather positive; and 3) the acceptance of the use of CDTs can be supported by practical rather than theoretical solutions. The result can add value and stimulate new research related to the usage of CDTs, potentially serving as a useful benchmark for other countries. Doi: 10.28991/esj-2022-SPER-015 Full Text: PDF